2018
DOI: 10.3390/ijms19124079
|View full text |Cite
|
Sign up to set email alerts
|

A Metabologenomic Approach Reveals Changes in the Intestinal Environment of Mice Fed on American Diet

Abstract: Intestinal microbiota and their metabolites are strongly associated with host physiology. Developments in DNA sequencing and mass spectrometry technologies have allowed us to obtain additional data that enhance our understanding of the interactions among microbiota, metabolites, and the host. However, the strategies used to analyze these datasets are not yet well developed. Here, we describe an original analytical strategy, metabologenomics, consisting of an integrated analysis of mass spectrometry-based metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 84 publications
0
46
1
Order By: Relevance
“…In order to obtain novel knowledge by combining the metabolome and microbiome analysis of the intestinal environment, a multi-omics approach could be a valuable tool for understanding the entire intestinal ecosystem, including the relationships among microbiota, metabolites and host. Additionally, it is considered that a multi-omics approach integrating metagenomics and metabolomics, called metabologenomics, can provide new information about the mechanisms underlying the key roles the microbiota plays in the varying conditions of the intestinal environment (Ishii et al, 2018).…”
mentioning
confidence: 99%
“…In order to obtain novel knowledge by combining the metabolome and microbiome analysis of the intestinal environment, a multi-omics approach could be a valuable tool for understanding the entire intestinal ecosystem, including the relationships among microbiota, metabolites and host. Additionally, it is considered that a multi-omics approach integrating metagenomics and metabolomics, called metabologenomics, can provide new information about the mechanisms underlying the key roles the microbiota plays in the varying conditions of the intestinal environment (Ishii et al, 2018).…”
mentioning
confidence: 99%
“…Similarly, a PCA analysis between different groups of proteins showed that the down-regulation of proteins related to energy metabolism was associated with an increase in the abundance of Bacteroidetes and Firmicutes after an eight week intervention with a cafeteria diet in rats (49% fat of total energy) [ 74 ]. Also, an animal study with an American diet (50% carbohydrate, 15% protein, and 35% fat, for nine weeks) compared to a normal diet (25–30% fat, for nine weeks), demonstrated that the amount butyrate in the stool (the difference between metabolites in two diets measured by PCA) was positively correlated (by correlation test and network analysis) with the abundance of butyrate-producing bacteria, Oscillospira and Ruminococcus (differences between microbiota between two diets by PCoA) [ 77 ]. Furthermore, a greater impact of gut microbiome compared to dietary intake (medium-fat and carbohydrate meal) was found on postprandial lipemia using a PCA analysis [ 70 ].…”
Section: Multi-omics Studies In Nutrition Researchmentioning
confidence: 99%
“…Ishii et al. developed an analytical strategy, termed metabologenomics, which consisted of MS‐based fecal metabolomics, metagenomics, and multi‐omics data integration (e.g., correlation, network analysis, and Procrustes analysis). Upon identification of differentially abundant metabolites, microbial taxa, and the predicted functions in American diet‐fed mice compared to controls, they demonstrated significant correlations between these alterations at different levels and showed that the consumption of high‐fiber diet can benefit the host through modulating the gut bacteria and their metabolites, even with a high‐fat diet.…”
Section: Integrative Multi‐omics For the Characterization Of Gut Micrmentioning
confidence: 99%
“…performed Procrustes analysis for the principal coordinates analysis (PCoA) of gut metagenome data and PCA of bio‐clinical data for obese individuals before and after dietary intervention, which showed that the structural shifting of the gut microbiota was significantly associated with the improvement of host health with dietary intervention . Procrustes analysis has also been used to compare the fecal metabolome and microbiome which revealed significant inter‐omic correlations Multiple Co‐inertia Analysis.…”
Section: Integrative Multi‐omics For the Characterization Of Gut Micrmentioning
confidence: 99%
See 1 more Smart Citation